HUBUNGAN KELINCAHAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KECEPATAN TENDANGAN SABIT ATLET PENCAK SILAT SILATURAHMI KALUMBUK KECAMATAN KURANJI KOTA PADANG - Rosmawati FIK-UNP; Darni FIK-UNP; Hilmainur Syampurma (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
The Problems this research were the weakened a scythe athletes Silahturahmi Kalumbuk Kec.Kuranji Padang.This research aims to to express what is the relationship agility and explosive power limb muscles together to a scythe athletes Silahturahmi Kalumbuk Kec.Kuranji Padang. Population research is athletes Silahturahmi Kalumbuk Kec.Kuranji Padang. Technique withdrawal sample with a total of sampling, so samples to research is established as many as 30 people. The result of the analysis data showed that there are relations together between agility and explosive power limb muscles together to a scythe athletes Silahturahmi Kalumbuk Kec.Kuranji Padang where obtained the first significant α=0,05 and contributing of 46,4%.